Kepasatian Penegakan Hukum Tindak Pidana Korupsi Pasca Disahkannya Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana - Harmelia, Harmelia; Kurnia, Ade (IJOCE: Indonesia Journal of Civic Education, 2025)
Criminal law reform through the National Criminal Code (KUHP) is carried out to protect and provide welfare to the community. Both are in line with the goals of the state as stated in the Preamble to the 1945 Constitution. Meanwhile, sociologically, the current development of criminal law has created criminal law outside the KUHP that is not based on appropriate criminal law formation policies, thus conflicting with the principle of legal certainty. To address this, comprehensive criminal law reform is needed to build a national criminal law system that embodies the mission of consolidation, decolonization, harmonization, democratization, and actualization of various legal developments. With the enactment of Law No. 1 of 2023 concerning the Criminal Code, this reform of criminal law, which also serves as the Indonesian National Criminal Code, is reflected. The enactment of the National Criminal Code also revokes several core articles (core crimes) of corruption that were previously specifically regulated in the Corruption Eradication Law. This undoubtedly creates uncertainty regarding the enforcement of corruption laws, which are regulated by both general and specific provisions.   Keywords: Legal certainty, corruption, National Criminal Code